2014
DOI: 10.1103/physrevlett.112.055505
|View full text |Cite
|
Sign up to set email alerts
|

Nanophononic Metamaterial: Thermal Conductivity Reduction by Local Resonance

Abstract: We present the concept of a locally resonant nanophononic metamaterial for thermoelectric energy conversion. Our configuration, which is based on a silicon thin film with a periodic array of pillars erected on one or two of the free surfaces, qualitatively alters the base thin-film phonon spectrum due to a hybridization mechanism between the pillar local resonances and the underlying atomic lattice dispersion. Using an experimentally fitted lattice-dynamics-based model, we conservatively predict the metamateri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
268
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 268 publications
(281 citation statements)
references
References 39 publications
10
268
2
1
Order By: Relevance
“…The pioneering works mainly studied how local resonances flatten phonon dispersion and open phononic bandgaps, which can suppress propagation of phonons at gigahertz frequencies. In the past few years, this idea expanded beyond the phononic bandgaps and researchers began dreaming about the suppression of phonons in the terahertz frequency range thus reducing the thermal conductivity of materials [30,32,33,55]. However, the Brillouin light scattering experiments could confirm changes in phonon dispersion only up to a few tens of gigahertz [31,48], which affects only a negligible part of the thermal phonon spectrum at room temperature.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The pioneering works mainly studied how local resonances flatten phonon dispersion and open phononic bandgaps, which can suppress propagation of phonons at gigahertz frequencies. In the past few years, this idea expanded beyond the phononic bandgaps and researchers began dreaming about the suppression of phonons in the terahertz frequency range thus reducing the thermal conductivity of materials [30,32,33,55]. However, the Brillouin light scattering experiments could confirm changes in phonon dispersion only up to a few tens of gigahertz [31,48], which affects only a negligible part of the thermal phonon spectrum at room temperature.…”
Section: Discussionmentioning
confidence: 99%
“…The data show that the pillar height ( t ) has no significant impact, at least for the pillars taller than several angstroms, Recently, Honarvar and Hussein [34] studied the height dependence in more details. They showed that even nanopillars of a few angstroms in height already reduce the thermal conductivity by more than 50%, but as nanopillars become taller this reduction gradually saturates.
10.1080/14686996.2018.1542524-F0004Figure 4.Example of a molecular dynamics model of a pillar-based PnC and the dependence of the thermal conductivity normalized by that of a membrane on the pillar height ( t ) found in Refs [33,34,55,58].
…”
Section: Simulations Of Heat Conductionmentioning
confidence: 95%
See 3 more Smart Citations